2015
DOI: 10.1016/j.neuron.2015.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Neural Regulation of Hematopoiesis, Inflammation, and Cancer

Abstract: Although the function of the autonomic nervous system (ANS) in mediating the “flight-or-fight” response was recognized decades ago, the crucial role of peripheral innervation in regulating cell behavior and response to the microenvironment has only recently emerged. In the hematopoietic system, the ANS regulates stem cell niche homeostasis, regeneration and fine-tunes the inflammatory response. Additionally, emerging data suggest that cancer cells take advantage of innervating neural circuitry to promote their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
182
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 153 publications
3
182
0
3
Order By: Relevance
“…The synaptic plasticity that we have identified in the adrenal may be involved in other conditions that involve robust sympathetic activation (11). For example, the baroreceptor reflex activates preganglionic neurons innervating norepinephrinesecreting chromaffin cells (47).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The synaptic plasticity that we have identified in the adrenal may be involved in other conditions that involve robust sympathetic activation (11). For example, the baroreceptor reflex activates preganglionic neurons innervating norepinephrinesecreting chromaffin cells (47).…”
Section: Discussionmentioning
confidence: 96%
“…These findings reveal a critical role for sympatho-adrenal synaptic plasticity in the CRR to hypoglycemia, and suggest that a failure to induce synaptic strengthening may lead to conditions associated with a loss of glycemic control (1, 3). More broadly, this type of sympathetic plasticity could regulate the activity of a growing list of unconventional autonomic targets, including hematopoietic stem cells and bone osteoblasts (11,12). …”
mentioning
confidence: 99%
“…These observations prompted investigations into how sympathetic tone affects the production and release of leukocytes from BM [61]. Indeed, the sympathetic nervous system has recently emerged as a key component and regulator of the stem cell niche [62]. …”
Section: Role Of the Pns In The Development Deployment And Homeostamentioning
confidence: 99%
“…As we cannot expound on these topics in depth within the scope of this article, we provide below only a brief overview highlighting a few examples and otherwise refer the reader to recent reviews [62, 235]. …”
Section: Neuro-immune Interactions During Infection and Diseasementioning
confidence: 99%
“…Interestingly, signals from the sympathetic nervous system regulate pericytes' function in the bone marrow microenvironment [29,30]. O'Farrell and colleagues showed that half of cardiac pericytes are located close to sympathetic neurons varicosities, implicating a possible role of noradrenergic regulation in pericytes' behavior [9].…”
Section: Perspectives/future Directionsmentioning
confidence: 99%